Pengaruh Konseling dengan Alat Bantu Pengambilan Keputusan (ABPK) Kepada Pasangan Usia Subur terhadap Pengetahuan Kepesertaan Keluarga Berencana di Puskesmas Asologaima Kab. Jayawijaya - Yuliani, Indah; Salmawati, Salmawati (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT According to WHO data, 2023 shows that there will be 1.9 billion women in the reproductive age group. Global contraceptive prevalence by any method is estimated at 65% and modern methods at 58.7%. The prevalence of PUS for family planning participants in Indonesia in 2023 will be 60.4%. Based on provincial distribution, the highest prevalence rate of family planning use is South Kalimantan (71.2%), and the lowest is Papua (10.5%). At the Asologaima Community Health Center, family planning coverage is still low, due to a lack of knowledge and interest in couples of childbearing age in choosing contraceptives. Efforts that can be made are by providing Communication, Information and Education (KIE) before family planning acceptors choose which contraception to use. To determine the effect of counseling with Decision Making Tools (ABPK) for couples of childbearing age on knowledge of family planning participation. Quasi experiment with a one group pretest-posttest design. The sampling technique uses random sampling. Data analysis used univariate and bivariate analysis with the Wilcoxon Signed Ranks Test. Before being given counseling with ABPK, the majority of respondents had poor knowledge, 66.3%, and after being given counseling with ABPK, the majority of respondents had good knowledge, 59.1%. There is an influence of counseling with decision making tools (ABPK) for couples of childbearing age on knowledge of family planning participation at the Asologaima Health Center, Jayawijaya Regency (p. value 0.003). There is an influence of counseling with decision-making aids (ABPK) for couples of childbearing age on knowledge of family planning participation. It is hoped that health workers can improve the quality of family planning services to mothers both through counseling and education about contraception using ABPK feedback sheets. Keywords: Counseling, Couples of Childbearing Age, Family Planning  ABSTRAK Menurut data WHO, 2023 menunjukkan bahwa sebanyak 1,9 miliar perempuan pada kelompok usia reproduksi. Prevalensi kontrasepsi global dengan metode apa pun diperkirakan sebesar 65% dan metode modern sebesar 58,7%. Prevalensi PUS peserta KB di Indonesia pada tahun 2023 sebesar 60,4%. Berdasarkan distribusi provinsi, angka prevalensi pemakaian KB tertinggi adalah Kalimantan Selatan (71,2%), dan terendah adalah Papua (10,5%). Di Puskesmas Asologaima cakupan KB masih rendah, dikarenakan kurangnya pengetahuan dan minat pasangan usia subur dalam pemilihan alat kontrasepsi. Upaya yang dapat dilakukan yaitu dengan memberikan Komunikasi, Informasi dan Edukasi (KIE) sebelum akseptor KB memilih kontrasepsi yang akan digunakan. Mengetahui pengaruh  konseling  dengan  Alat  Bantu  Pengambilan Keputusan (ABPK) kepada pasangan usia subur terhadap pengetahuan kepesertaan keluarga berencana. Quasi experiment  dengan rancangan one group pretest-posttest design. Teknik pengambilan sampel menggunakan random sampling. Analisa data menggunakan analisa univariat dan bivariat dengan Uji Wilcoxon Signed Ranks Test. Sebelum diberikan konseling dengan ABPK mayoritas responden berpengetahuan kurang 66,3% dan sesudah diberikan konseling dengan ABPK mayoritas responden berpengetahuan baik 59,1%. Ada pengaruh  konseling dengan  alat  bantu  pengambilan keputusan (ABPK) kepada pasangan usia subur terhadap pengetahuan kepesertaan keluarga berencana di Puskesmas Asologaima Kabupaten Jayawijaya (p. value 0,003). Ada pengaruh  konseling dengan  alat  bantu  pengambilan keputusan (ABPK) kepada pasangan usia subur terhadap pengetahuan kepesertaan keluarga berencana. Diharapkan tenaga kesehatan dapat meningkatkan mutu pelayanan keluarga berencana kepada ibu-ibu baik melalui konseling maupun penyuluhan tentang kontrasepsi dengan menggunakan lembar balik ABPK. Kata Kunci: Konseling, Pasangan Usia Subur, Keluarga Berencana